DETERMINASI FAKTOR-FAKTOR ARROGANCE SEBAGAI PERSPEKTIF FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN - Yovita, Monika; Suryani, Elly (Jurnal Riset Akuntansi Politala, 2024)
Financial statement fraud is the misstatement or omission of amounts or deliberate disclosure with the intent of deceiving users of financial statements. Pentagon fraud is the factors that cause fraud through five elements: pressure, opportunity, rationalization, competence and arrogance. Arrogance is an attitude of arrogance that exists in a human being so that he considers that he is capable of cheating. This study was conducted to identify whether arrogance factors namely CEO Compensation, CEO Exposure and CEO Power have an effect on financial statement fraud. This research uses secondary data on the annual financial statements of manufacturing sector companies listed on the Indonesia Stock Exchange for 2017-2021. This research is quantitative with data collection techniques using purposive sampling with a total sample of 77 companies. The logistic regression research method is processed with Eviews 12 software. The results of this study show that CEO Power proxied with duality and CEO Exposure proxied with Photograph in Annual Report negatively affect financial statement fraud in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2021.